Unified propagation model for Wi-Fi, UMTS and WiMAX planning in mixed scenarios - Varela, Frederico (2010)
This paper presents an unified and empirical propagation model to obtain the received power in mixed scenarios, with outdoor and indoor environments, or in a scenario with only one kind of environment, either for an urban, sub-urban or rural scenario, with or without vegetation. This unified model is called the Lisbon University Institute (LUI) one and can be included into planning tools for wireless communication systems. The developed model is suitable for Path Loss prediction in mobile, as well as fixed wireless network systems, e.g., Wireless Fidelity, Universal Mobile Telecommunications System and Worldwide Interoperability for Microwave Access, considering Line-of-Sight or Non-Line-of-Sight propagation conditions.